Purification of Used Cooking Oil by Alkali Neutralization and Bleaching of Bayah Natural Zeolite - hendi, Endang Su; Rusdi, Rusdi; Alam, Bagja Nur; Nurbaeti, Siti (Jurnal Bahan Alam Terbarukan, 2021)
Cooking oil that is used repeatedly at high temperatures will reduce the quality of cooking oil. This will trigger the hydrolysis and oxidation processes that will change the characteristics of the oil, such as an increase in free fatty acid levels and peroxide numbers. Purification of used cooking oil can be carried out physically and chemically. The physical purification of oil is carried out by using adsorbents, while chemically purification process is carried out with an alkaline solution. Physically, natural materials such as zeolite can be used, where zeolite is a natural rock or mineral which chemically has a large surface area to be used in the adsorption process. Chemically with alkaline solution you can use sodium hydroxide (NaOH). In this study, used cooking oil is purified by three stages of the process, namely despicing, neutralization and bleaching to comply with the SNI quality standards. The purpose of this study was to determine the optimum operating conditions for the purification of used cooking oil in accordance with the quality standards for cooking oil. based on the results obtained by adding a NaOH concentration of 19% in the neutralization process and a zeolite concentration of 90% can reduce the acid number value of 2.4 mg NaOH/gr, the peroxide number is 7 mekO2/kg, the color degradation of used cooking oil is 51.83%.